PERKEMBANGAN PENDIDIKAN MASA DINASTI UMAYYAH II DAN PERANNYA TERHADAP PENDIDIKAN ISLAM - Mahya, Izzatul; Azizah, Muanisa; Hidayah, Nafisah (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2025)
The background Andalusia, which is now called Spain, is a great country whose progress is inseparable from the role of the Umayyad II Dynasty. Islam experienced its heyday in Andalusia, many advances were achieved by the Umayyad II Dynasty, especially in the field of education. Andalusia became an advanced scientific center, covering the fields of theology, law, literature, art, and science. This article aims to examine more deeply the development of education during the Second Umayyad Dynasty in Andalusia and its role in the Islamic education system today. Islam in Andalusia gave birth to Muslim scholars whose works still exist today. This research uses the library research method by making library materials such as books, or literature from previous research such as articles, journals, and so on as data sources. The results show that the system that developed during the Second Umayyad Dynasty not only gave birth to a superior scientific center, but also formed an integrative and multidisciplinary model of Islamic education. The relevance to education in the modern era is quite significant. Almost all disciplines that exist today are influenced by education during the Second Umayyad Dynasty so that it has contributed quite a lot.